M i c r o o r g a n i s m s in S e m i n a l S a m p l e s w i t h a n d w i t h o u t P y o s p e r m i a : Relevance f o r A s s i s t e d R e p r o d u c t i o n T e c h n o l o g i e s (ART) - Kaluarachchi, A; Seneviratne, H.R; Wijeratne, S (My University)
Pyospermia is s a id to i n d i c a te male genital infection Mic.roorqair.iiv, may colonize Hie seminal plasma and therefore no-exist with spermatozoa in the lumen or may invade the genital tract wall causing an inflammation. PyospnniKi w o u l d be morn likely in the latter. . In our experience inspite ot prior antibiotic treatment seminal microorganisms have seriously affected the g r o w t h and survival of embryos at ART This study aims to determine